Empowerment of Health Cadres and Families in Preventing Gadget Addiction Among Toddlers - sartika, dona; Suartini, Endang (POLTEKKES KEMENKES BANTEN, 2024)
Gadget addiction can have a negative impact on a toddler’s development. The role of the family is needed to prevent gadget addiction. This Community Service aims to empower health cadres and families in preventing gadget addiction in toddlers. The service method involves providing assistance and providing education to health cadres and families, divided into four stages, namely: planning, preparation, implementation, and monitoring and evaluation. Results: there was a decrease in the average time toddlers used gadgets to 23.5 minutes a day, and there was an increase in family skills in monitoring gadget use with an average score of 34.5. The conclusion of this service activity is the implementation of empowerment of health cadres and families in efforts to prevent gadget addiction in toddlers in the Working Area of Puskesmas Neglasari, Tangerang City.